Adaptation and validation of a Chinese version of Patient Health Engagement Scale for patients with chronic disease - Zhang, Yaying; Graffigna, Guendalina; Bonanomi, Andrea; Choi, Kai-chow; Barello, Serena; Mao, Pan; Feng, Hui (Frontiers in Psychology, 2017)
The Patient Health Engagement Scale (PHE-s) was designed to assess the emotional and psychological attitudes of patients’ engagement along their healthcare management journey. The aim of this study was to validate a culturally adapted Chinese version of the PHE-s (CPHE-s). Three hundred and seventy-seven participants were recruited from eight community health centers in a sample of patients with chronic disease in Hunan Province, China. The original Italian PHE-s was translated into Mandarin Chinese using a standardized forward–backward translation. The Rasch model was utilized and presented uni-dimensionality and good items fitness of the PHE-s. The internal consistency and intra-class correlation coefficients were 0.89 and 0.68, respectively. Both principal component analysis and confirmatory factor analysis supported a single-factor structure of the PHE-s. In testing the external validity, the PHE-s showed a significant moderate correlation with patient activation but not with medicine adherence behavior, which requires further exploration. The result suggested that the PHE-s is a reliable and valid instrument to assess the level of patient engagement in his or her own health management among chronic patients in China. Further analysis of reliability and validity should be assessed among other patient cohorts in China, and future directions for testing changes after patient engagement interventions should be developed by exploring some clinical relevance.